Detection of Cronobacter sakazakii (Enterobacter sakazakii) in powdered food infants (PIF) and raw milk in Iraq (Baghdad Science Journal, 2015)
This study was conducted to detect C.sakazakii PIF and raw milk. Two hundred samples of PIF were taken from the infected hospital infants who used this type of milk and from the local markets in addition to 16 sample of raw milk were collected. The study is the first to report the isolation of C. sakazakii and Enterobacter spp. from raw milk in Iraq. The distribution of C.sakazakii and Enterobacter spp. among the presumptive isolates using Vitek-GN2 system gave 1/16(6.25%) isolates of C.sakazakii and 4/16 (25%) isolates of Enterobacter spp. Enterobacter spp. isolates include (E.cloacae ssp. cloacae and E.cloacae ssp. dissolvens, E.hormaechei, and E.ludwigii) that isolate from raw milk Differences in between percentages of each isolate persence were non-significant (P